Ultra-structural analysis of breast tissue - Round, A. R. (Cranfield University, 2007)
Previous research has shown that diagnostic information could be obtained from small angle X-ray scattering from breast tissues. The observed differences were attributed to two possible causes, the production of a new type of collagen around tumours and the action of matrix metalloproteinases degrading the collagen around tumours. Using both synchrotron radiation and conventional X-ray sources data was collected to investigate these hypotheses. 225 X-ray scattering profiles were collected from breast tissue samples from 82 individual patients using synchrotron radiation. The differences between normal, malignant and benign tissues were investigated and structural differences in the collagen were determined. The effects of metalloproteinase action on collagen were also investigated and computer modelling was used to simulate the diffraction profiles from collagen with structural alterations. The structural differences in diseased tissues were attributed to a difference in the structure of collagen which was observed as a reduction in peak intensity and increased axial D spacing (0.3 nm increase in D period) compared to normal tissues. The differences between malignant and benign disease were attributed to metalloproteinase action degrading the collagen around tumours. Automatic classification was applied using principal component analysis to tissue samples from up to 6 cm away from the tumour site, approximately 90 % of the tissue samples at 6 cm were classified as cancer using the X-ray scattering profile but which were diagnosed as normal by standard histopathological methods. The results of this research have shown that X-ray scattering profiles contain diagnostic information relating to the structure of collagen. The changes associated with disease may be observed at up to 6 cm from the tumour site and that these differences in the X-ray scattering profile may be measured using a conventional X-ray source.